PERSEPSI MAHASISWA TERHADAP VIDEO MONOLOG SEBAGAI ALTERNATIF TUGAS DALAM PEMBELAJARAN DARING - Diah Anugrah Dipuja (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2020)
The purpose of this study was to determine students' perceptions of monologue videos as alternative tasks in online learning. Monologue videos are one of various online learning alternatives which are assumed to increase student activity and creativity in learning so that online learning becomes more effective. Information about student perceptions regarding the effectiveness of monologue videos in online learning is needed to develop online learning to become better. This research was conducted by giving a questionnaire via google form to Biology education students as research respondents. From the research that has been done, the results showed that the application of monologue videos by students is considered effective as an alternative to online learning because it could increase student activity, creativity and motivation. However, there were some challenges and obstacles such as difficulties in making video scripts and video editing as well as network constraints and internet quota. Thus, it can be concluded that the application of video monologues as an alternative task in online learning were considered effective by students and can be developed further in other subjects.